Consumption of fermented dairy products is associated with lower anxiety levels in Azorean university students - Sousa, Rodrigo J. M.; Baptista, José A. B.; Silva, Célia C. G. (Frontiers in Nutrition, 2022)
A growing number of studies have found that the gut microbiota is involved in a variety of psychological processes and neuropsychiatric disorders, which include mood and anxiety disorders. Consumption of dairy products may contain bioactive compounds and probiotic bacteria with various therapeutic benefits. The aim of the study was to investigate possible associations between the frequency of consumption of different types of dairy products and the state of anxiety in university students. The subjects were 311Azorean university students, 231 women and 80 men, with an average age of 20.5 years. Subjects completed a quantitative questionnaire on the frequency of dairy product consumption and a short version of the Spielberger State-Trait Anxiety Inventory (STAI) test. Among dairy products, semi-skimmed milk was the most commonly consumed, followed by cheese (ripened), drinking yoghurt, skim milk, and set yoghurt, while fresh cheese, whole milk, and dairy ice cream were the least common. Discriminant analysis showed that consumption of fermented products (yoghurt and cheese) was significantly higher (P < 0.05) in the group with low anxiety level (score < 40 in STAI test) than in the group with higher anxiety level (score ≥ 40). In this analysis, 62.4% of the initially grouped cases were correctly classified according to the frequency of fermented products consumption. No correlations were found between anxiety and unfermented dairy products. The results indicate that the consumption of fermented dairy products has a positive effect on reducing anxiety in young Azorean university students.